A study on the Concentration‐dependent Relaxometric Transition in Manganese Oxide Nanocolloid as MRI Contrast Agent. Issue 25 (4th July 2019) - Khodaei, Azin; Malek, Mahrooz; Hosseini, Hamid Reza Madaah; Delavari H, Hamid; Vahdatkhah, Parisa
Abstract: A green precipitation method has been used for the synthesis of ultra‐small APTMS‐mPEG conjugated Mn3 O4 nanoparticles. Spherical cores in the uniform size of 4±1 nm were characterized by HRTEM. Zeta potential of −45 mV and the invariant turbidimetry results during the time, confirmed super‐stability of the colloids. MRI relaxometry by 1.5 T scanner represented two values of r1 = 8.23 s −1 mM −1 and r1 =7.3 s −1 mM −1 for diluted and concentrated samples. The r2 /r1 ratio was also decreased from 11.86 to 6.9 by dilution of colloids. Particle aggregation and motional narrowing phenomena led to a dual T1 /T2 contrast agent in the Mn ion concentrations of more than 0.2 mM. The optimum concentration of Mn ion for maximum dual signal intensity was estimated about 0.4 mM which is two times less than commercial Gd–DTPA. Cytotoxicity was examined through MTT assay and respectively, showed high cell viability at 48 h incubation. Overall, a potential dual T1 /T2 contrast agent was developed for early‐stage detection. Abstract : The main aim of this research was to develop a dual T1 /T2 contrast agent based on PEGylated APTMS‐coated Mn3 O4 nanoparticles. The Biocompatible ultra‐small synthesized nanoparticles showed super‐stable colloidal behaviour. The relaxometric properties of this colloid depended on Mn ion concentration, which was discussed based on "particle aggregation" and "motional narrowing" concepts. Changing the concentration of nanoparticles in this colloid led to a T1 ‐T1 /T2 switchable contrast agent. The optimum concentration of manganese in the colloid was also determined according to the maximum signal intensity.